Copper-based active brazing alloy powder and preparation method and application thereof

By modifying the surface of copper-based active brazing alloy powder and introducing silver and aluminum elements, the problems of insufficient bonding strength and poor dispersion of copper-based active brazing powder are solved, and the quality and efficiency of brazing are significantly improved.

CN119733984AActive Publication Date: 2025-04-01HUNAN METALLURGY MATERIAL RES INST

Patent Information

Application Number
CN202411469225.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-04-01
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The existing copper-based active brazing powders have problems such as insufficient brazing bonding strength, easy oxidation, and easy agglomeration, resulting in poor dispersion, which leads to inactivation of active elements, poor dispersion of solder paste, and uneven solder distribution.

Method used

By modifying the surface of copper-based active brazing alloy powder, its oxidation resistance and dispersion are improved, and two reinforced elements, silver and aluminum are introduced, to improve the solderability and titanium activity of the brazing material.

Benefits of technology

It significantly improves the oxidation resistance, dispersion and welding properties of the powder, reduces the settlement rate of the metal powder, and improves the bonding strength of the brazing and the sintering quality of the ceramic copper clad substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733984A_ABST
    Figure CN119733984A_ABST
Patent Text Reader

Abstract

The invention provides copper-based active brazing alloy powder and a preparation method and application thereof. The alloy powder comprises 55.0%-68.0% of copper, 6.0%-17.0% of tin, 5.0%-20.0% of silver, 1.0%-10.0% of titanium, 0.1%-2.0% of aluminum, and the total amount of impurity elements is smaller than 0.3%. The preparation method comprises the following steps: preparing raw materials according to alloy components, preparing alloy powder by adopting smelting and vacuum gas atomization, and carrying out surface modification and degumming. The oxidation resistance of the prepared alloy powder is improved by more than one time, the Hall flow velocity of the powder is reduced by more than 20%, the apparent density of the powder is increased by more than 15%, the dispersity among powder particles is obviously improved, dispersion homogenization of the metal powder is facilitated, and the sedimentation rate is reduced. By introducing the two strengthening elements of silver and aluminum, the weldability of the copper-based brazing filler metal is improved, combination of the copper element and the active element titanium is effectively inhibited, and then the activity of the titanium element is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of welding, and in particular to a copper-based active brazing alloy powder and a preparation method and application thereof. Background Art

[0002] Brazing has the advantages of lower welding temperature than the base material, which keeps the base material's structural characteristics uniform, more precise assembly and connection, and keeps the overall structure, shape and size of the workpiece. It has a simple process and is easy to connect different materials. It can weld complex and special workpieces, and even connect multiple seams and parts at one time. It has become an important connection method between metal and non-metal dissimilar materials, such as ceramic copper-clad substrates, diamond tools, ceramics and Kovar alloys, and other dissimilar materials.

[0003] In the sealing of ceramics and metals, general solders cannot directly wet ceramics, so active solders are needed to promote the bonding of ceramics and metals. Commonly used brazing materials are mainly silver-copper-titanium-based (AgCuTi), copper-tin-titanium-based (CuSnTi), etc. Silver-copper-titanium-based active solder is a universal solder for ceramic brazing, which can wet almost all ceramics. It has wettability for carbon materials, carbon composite materials, glass, etc., but its high production cost limits its large-scale application. In addition, for the application field of electronic devices such as ceramic copper-clad substrates that require etching, silver-copper-titanium-based active solders have problems such as low etching efficiency and easy migration of silver ions. Therefore, low-cost copper-tin-titanium-based active solders have become a potential choice. At present, the types of copper-based active solders that have been explored by scientific researchers include CuSnTi, CuZnTi and CuTi. At present, there are still problems that need to be solved, such as insufficient brazing bonding strength of copper-based active solders and high sintering void rate of ceramic copper-clad substrates.

[0004] Solder paste is currently the main industrial application form of active brazing alloys. The traditional powder mixing method has problems such as insufficient powder uniformity, long-term mixing may lead to powder oxidation, increased impurity content, and differences in different types of powders during solder paste production leading to stratification during solder paste transportation and storage. Therefore, it is an ideal choice to prepare solder paste in the form of multi-element alloy powder. Active brazing alloy powders have problems such as element segregation, high impurity content, easy oxidation of active elements, and powder agglomeration during the production process, which will cause the inactivation of active elements, poor solder paste dispersibility, and uneven solder distribution, which will affect the volatilization of organic matter in the solder paste.

[0005] Therefore, it is necessary to develop a new type of copper-based active brazing alloy powder to address the problems of insufficient brazing bonding strength, easy oxidation and agglomeration of copper-based active brazing powder, resulting in poor dispersion, which in turn leads to inactivation of active elements, poor dispersibility of solder paste, and uneven distribution of solder. Summary of the invention

[0006] The present invention provides a copper-based active brazing alloy powder and a preparation method and application thereof, the purpose of which is to solve the above-mentioned problems existing in the background technology.

[0007] In order to achieve the above-mentioned purpose, the embodiment of the present invention provides a copper-based active brazing alloy powder and its preparation method and application. The present invention improves the antioxidant capacity of the alloy powder by more than 1 times through modification treatment on the surface of the alloy powder, reduces the powder Hall flow velocity by more than 20%, increases the powder bulk density by more than 15%, and significantly improves the dispersibility between the powder particles, which is conducive to the dispersion and homogenization of the active brazing alloy powder in the subsequent paste making process, and reduces the sedimentation rate of the metal powder. In addition, compared with the commercial copper-tin-titanium active brazing alloy powder, the copper-based active brazing alloy powder prepared by the present invention improves the weldability of the copper-based brazing material by introducing two strengthening elements, silver and aluminum, and effectively inhibits the combination of copper elements and active element titanium, thereby improving the activity of titanium elements; compared with the commercial silver-copper-titanium active brazing alloy powder, the lower silver content greatly reduces the material cost of the brazing material, and at the same time, the strengthening effect of tin and aluminum elements on the copper matrix can weaken the influence of the reduction of silver content on the brazing strength.

[0008] An object of an embodiment of the present invention is to provide a copper-based active brazing alloy powder, which comprises the following components in percentage by mass: 55.0% to 68.0% copper, 6.0% to 17.0% tin, 5.0% to 20.0% silver, 1.0% to 10.0% titanium, 0.1% to 2.0% aluminum, and the total amount of impurity elements is less than 0.3%.

[0009] By adding 6.0% to 17.0% tin, the brazing temperature of the solder can be effectively reduced. When the tin content is 6 to 17%, the microstructure of the cast solder is mainly composed of α-Cu solid solution with a small amount of titanium dissolved, and the low-melting point eutectic structure accounts for a small proportion. As the tin content gradually increases, the α-Cu solid solution in the cast solder decreases, the low-melting point eutectic structure increases, and it is significantly coarsened, which reduces the performance of the solder. Therefore, the comprehensive performance of the solder with 6.0% to 17.0% tin is better, such as melting temperature, wettability, shear strength, and microhardness. If the tin content is too low, the melting temperature of the solder is high, the brazing wettability is significantly reduced, and the solid solution strengthening effect is poor; if the tin content is too high, the high vapor pressure tin element is easy to volatilize during use and then pollute the device, the material has a low microhardness, and the thermal conductivity of the solder is reduced. Adding 5.0% to 20.0% silver can form a β-Ag+α-Cu network structure in the copper matrix, which is beneficial to improving the strength and other properties of the material. When the silver content is too low, the strengthening effect of silver is weak, and when the silver content is too high, the production cost of the material will increase. In addition, the addition of silver can reduce defects such as brazing voids and enhance the wettability of the brazing filler metal. When the titanium content of the cast brazing filler metal increases from 1% to 10%, Cu 41 Sn 11The phases of CuSn3Ti5 and CuSn5 are significantly reduced, the tin content in the α-Cu solid solution is reduced, and the titanium content is increased, which is beneficial to improve the shear strength of the cast solder. When the titanium content continues to increase, the large block CuSn3Ti5 intermetallic compounds in the cast solder increase and increase in size, resulting in increased brittleness of the solder and deterioration of the shear resistance of the solder. The addition of 0.1% to 2.0% aluminum refines the dendritic β-Sn area and expands the interdendritic eutectic area. At the same time, the addition of aluminum inhibits the formation of compounds such as Ag3Sn and Cu6Sn5. Ag3Al, CuAl2 and aluminum-rich phases appear in the solder. The fine Ag3Al compound particles are about 3μm in size and are neatly distributed in the interdendritic area. The size decreases with the increase of Al addition. Ag3Al particles can effectively inhibit the generation of cracks as an obstacle to dislocation expansion, so that the solder has higher strength and greater tensile stress. In addition, when aluminum is melted and added to the brazing filler metal, aluminum atoms tend to preferentially combine with copper atoms to form aluminum-copper phase compounds, weakening the combination of copper and titanium, thereby improving the activity of titanium to a certain extent. If the aluminum content is too low, there will be fewer fine Ag3Al and other strengthening phases, and the strengthening effect will not be obvious; if the content is too high, the coarse CuAl2 and aluminum-rich phases will increase, reducing the performance of the brazing filler metal.

[0010] Preferably, the following components are included in percentage by mass: 55.0% to 68.0% copper, 6.0% to 17.0% tin, 5.0% to 19.0% silver, 1.0% to 10.0% titanium, 0.1% to 2.0% aluminum, and the total amount of impurity elements is less than 0.3%.

[0011] Preferably, the following components are included in percentage by mass: 55.0% to 68.0% copper, 6.0% to 17.0% tin, 5.0% to 19.0% silver, 2.0% to 10.0% titanium, 0.1% to 2.0% aluminum, and the total amount of impurity elements is less than 0.3%.

[0012] Another object of an embodiment of the present invention is to provide a method for preparing the above-mentioned copper-based active brazing alloy powder, comprising the following steps:

[0013] S1. Place copper, tin, silver, aluminum and titanium in a vacuum medium frequency induction furnace for smelting, and stir the raw materials after melting to obtain an alloy melt;

[0014] S2. The alloy melt is vacuum atomized using high-purity argon gas to obtain an alloy powder;

[0015] S3. The surface modifier obtained by mixing the organic solvent and the modifier is mixed with the alloy powder in a vacuum mixer to obtain a modified alloy powder;

[0016] S4. Remove the organic solvent from the modified alloy powder to obtain copper-based active brazing alloy powder.

[0017] Preferably, in step S1, the smelting temperature is 1100-1200°C, the vacuum degree is ≤40Pa, and the stirring time after the raw materials are melted is 5-30min.

[0018] Preferably, in step S2, the purity of the high-purity argon gas is ≥99.999%; the spray angle of the atomizer is 30° to 50°, the atomization gas pressure is 3 to 7 MPa, the atomization temperature is 900 to 1150°C, and the atomization rate is 4 to 6 kg / min.

[0019] Preferably, in step S3, the organic solvent includes one or more of methyl ethyl ketone, ketone, ethanol, acetone, and ether, and the modifier includes one or more of hexadecanoic acid hexadecyl ester, methyl palmitate, and palmitic acid; the ratio of the volume of the organic solvent to the mass of the modifier is 50 to 1100:1; the ratio of the mass of the alloy powder to the volume of the organic solvent is 6 to 20:1. Preferably, the ratio of the volume of the organic solvent to the mass of the modifier is 700:1, 800:1, 900:1, or 1000:1.

[0020] Preferably, in step S3, the temperature is 30-45°C; the mixing time of the organic solvent and the modifier is 2-10 minutes; and the mixing time of the surface modifier and the alloy powder is 15-30 minutes.

[0021] Preferably, in step S4, the removal temperature is 40-65° C., the vacuum degree is 50-100 Pa, and the removal time is 5-20 min.

[0022] The embodiments of the present invention also provide the use of the above-mentioned copper-based active brazing alloy powder or the copper-based active brazing alloy powder obtained by the above-mentioned preparation method in the brazing field, and the brazing field includes the fields of ceramic copper-clad substrates, diamond tools, ceramics and Kovar alloys.

[0023] The above scheme of the present invention has the following beneficial effects:

[0024] (1) Compared with the unmodified alloy powder, the antioxidant capacity of the modified alloy powder of the present invention is improved by more than 1 times, the powder Hall flow velocity is reduced by more than 20%, the powder loose density is increased by more than 15%, and the dispersion between powder particles is significantly improved, which is beneficial to the dispersion and homogenization of the active brazing alloy powder in the subsequent paste making process and reduces the sedimentation rate of the metal powder.

[0025] (2) Compared with commercial copper-tin-titanium active brazing alloy powder, the copper-based active brazing alloy powder prepared by the present invention improves the weldability of the copper-based solder by introducing two strengthening elements, silver and aluminum, effectively inhibits the combination of copper element and active element titanium, and thus improves the activity of titanium element; compared with commercial silver-copper-titanium active brazing alloy powder, the lower silver content greatly reduces the material cost of the solder, and at the same time, the strengthening effect of tin and aluminum elements on the copper matrix can weaken the influence of the reduced silver content on the brazing strength.

[0026] (3) The copper-based active brazing alloy powder of the present invention is suitable for brazing in the fields of ceramic copper-clad substrates, diamond tools, ceramics and Kovar alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 This is the microscopic morphology of a copper-based active brazing alloy powder according to Example 3 of the present invention.

[0029] Figure 2 The microscopic morphology of a copper-based active brazing alloy powder according to Comparative Example 1 of the present invention.

[0030] Figure 3 The microscopic morphology of a copper-based active brazing alloy powder of Comparative Example 2 of the present invention.

[0031] Figure 4 This is the void rate test result of brazing a silicon nitride ceramic copper-clad substrate with a copper-based active brazing alloy powder prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0032] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0033] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0034] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0035] The raw materials mentioned in the article, such as "copper, tin, silver, aluminum, and titanium", are all metal single substances. The unit of mass is "g" and the unit of volume is "mL". The "B" mentioned in the comparative example represents hard solder, see "GBT6418-2008-Copper-based solder" and other relevant national standards, which is also the commonly used expression method in the industry.

[0036] The core problems to be solved by the present invention are: (1) the copper-based active powder prepared by direct vacuum gas atomization has poor dispersibility, no fluidity, and a small bulk ratio, which is not conducive to the preparation and performance of the subsequent paste; (2) when commercial copper-tin-titanium active brazing alloys are used to braze ceramic copper-clad substrates and other materials, the material has poor wettability, high void rate, and insufficient bonding strength. The addition of silver content can improve the above-mentioned properties, but will greatly increase the cost, etc., thereby providing a copper-based active brazing alloy powder and its preparation method and application.

[0037] An object of an embodiment of the present invention is to provide a copper-based active brazing alloy powder, which comprises the following components in percentage by mass: 55.0% to 68.0% copper, 6.0% to 17.0% tin, 5.0% to 20.0% silver, 1.0% to 10.0% titanium, 0.1% to 2.0% aluminum, and the total amount of impurity elements is less than 0.3%.

[0038] By adding 6.0% to 17.0% tin, the brazing temperature of the solder can be effectively reduced. When the tin content is 6 to 17%, the microstructure of the cast solder is mainly composed of α-Cu solid solution with a small amount of titanium dissolved, and the low-melting point eutectic structure accounts for a small proportion. As the tin content gradually increases, the α-Cu solid solution in the cast solder decreases, the low-melting point eutectic structure increases, and it is significantly coarsened, which reduces the performance of the solder. Therefore, the comprehensive performance of the solder with 6.0% to 17.0% tin is better, such as melting temperature, wettability, shear strength, and microhardness. If the tin content is too low, the melting temperature of the solder is high, the brazing wettability is significantly reduced, and the solid solution strengthening effect is poor; if the tin content is too high, the high vapor pressure tin element is easy to volatilize during use and then pollute the device, the material has a low microhardness, and the thermal conductivity of the solder is reduced. Adding 5.0% to 20.0% silver can form a β-Ag+α-Cu network structure in the copper matrix, which is beneficial to improving the strength and other properties of the material. When the silver content is too low, the strengthening effect of silver is weak, and when the silver content is too high, the production cost of the material will increase. In addition, the addition of silver can reduce defects such as brazing voids and enhance the wettability of the brazing filler metal. When the titanium content of the cast brazing filler metal increases from 1% to 10%, Cu 41 Sn 11The phases of CuSn3Ti5 and CuSn5 are significantly reduced, the tin content in the α-Cu solid solution is reduced, and the titanium content is increased, which is beneficial to improve the shear strength of the cast solder. When the titanium content continues to increase, the large block CuSn3Ti5 intermetallic compounds in the cast solder increase and increase in size, resulting in increased brittleness of the solder and deterioration of the shear resistance of the solder. The addition of 0.1% to 2.0% aluminum refines the dendritic β-Sn area and expands the interdendritic eutectic area. At the same time, the addition of aluminum inhibits the formation of compounds such as Ag3Sn and Cu6Sn5. Ag3Al, CuAl2 and aluminum-rich phases appear in the solder. The fine Ag3Al compound particles are about 3μm in size and are neatly distributed in the interdendritic area. The size decreases with the increase of Al addition. Ag3Al particles can effectively inhibit the generation of cracks as an obstacle to dislocation expansion, so that the solder has higher strength and greater tensile stress. In addition, when aluminum is melted and added to the brazing filler metal, aluminum atoms tend to preferentially combine with copper atoms to form aluminum-copper phase compounds, weakening the combination of copper and titanium, thereby improving the activity of titanium to a certain extent. If the aluminum content is too low, there will be fewer fine Ag3Al and other strengthening phases, and the strengthening effect will not be obvious; if the content is too high, the coarse CuAl2 and aluminum-rich phases will increase, reducing the performance of the brazing filler metal.

[0039] Preferably, the following components are included in percentage by mass: 55.0% to 68.0% copper, 6.0% to 17.0% tin, 5.0% to 19.0% silver, 1.0% to 10.0% titanium, 0.1% to 2.0% aluminum, and the total amount of impurity elements is less than 0.3%.

[0040] Preferably, the following components are included in percentage by mass: 55.0% to 68.0% copper, 6.0% to 17.0% tin, 5.0% to 19.0% silver, 2.0% to 10.0% titanium, 0.1% to 2.0% aluminum, and the total amount of impurity elements is less than 0.3%.

[0041] Another object of an embodiment of the present invention is to provide a method for preparing the above-mentioned copper-based active brazing alloy powder, comprising the following steps:

[0042] S1. Place copper, tin, silver, aluminum, and titanium in a vacuum medium frequency induction furnace for smelting, and stir the raw materials after melting to obtain an alloy melt;

[0043] S2. The alloy melt is vacuum atomized using high-purity argon gas to obtain an alloy powder;

[0044] S3. The surface modifier obtained by mixing the organic solvent and the modifier is mixed with the alloy powder in a vacuum mixer to obtain a modified alloy powder;

[0045] S4. Remove the organic solvent from the modified alloy powder to obtain copper-based active brazing alloy powder.

[0046] Preferably, in step S1, the smelting temperature is 1100-1200°C, the vacuum degree is ≤40Pa, and the stirring time after the raw materials are melted is 5-30min.

[0047] Preferably, in step S2, the purity of the high-purity argon gas is ≥99.999%; the spray angle of the atomizer is 30° to 50°, the atomization gas pressure is 3 to 7 MPa, the atomization temperature is 900 to 1150°C, and the atomization rate is 4 to 6 kg / min.

[0048] Preferably, in step S3, the organic solvent includes one or more of methyl ethyl ketone, ketone, ethanol, acetone, and ether, and the modifier includes one or more of hexadecanoic acid hexadecyl ester, methyl palmitate, and palmitic acid; the ratio of the volume of the organic solvent to the mass of the modifier is 50 to 1100:1; the ratio of the mass of the alloy powder to the volume of the organic solvent is 6 to 20:1. Preferably, the ratio of the volume of the organic solvent to the mass of the modifier is 700:1, 800:1, 900:1, or 1000:1.

[0049] Preferably, in step S3, the temperature is 30-45°C; the mixing time of the organic solvent and the modifier is 2-10 minutes; and the mixing time of the surface modifier and the alloy powder is 15-30 minutes.

[0050] Preferably, in step S4, the removal temperature is 40-65° C., the vacuum degree is 50-100 Pa, and the removal time is 5-20 min.

[0051] The embodiments of the present invention also provide the use of the above-mentioned copper-based active brazing alloy powder or the copper-based active brazing alloy powder obtained by the above-mentioned preparation method in the brazing field, and the brazing field includes the fields of ceramic copper-clad substrates, diamond tools, ceramics and Kovar alloys.

[0052] The following will describe the invention through specific embodiments.

[0053] Example 1

[0054] The present embodiment provides a copper-based active brazing alloy powder, whose chemical composition, by mass percentage, includes: 14.0% Sn, 15.0% Ag, 1.2% Al, 5.0% Ti, the total amount of impurity elements is less than 0.3%, and the rest is copper.

[0055] The method for preparing the copper-based active brazing alloy powder comprises the following steps:

[0056] (1) copper, tin, silver, aluminum and titanium are placed in a vacuum induction furnace, and the raw materials are completely melted and stirred for 10 minutes under medium frequency induction mode (80-90 kW, 900-1050 Hz) and vacuum degree 20-30 Pa to obtain a homogenized alloy melt;

[0057] (2) High-purity argon (purity ≥ 99.999%) is used to vacuum gas atomize the homogenized alloy melt to obtain alloy powder; the spray angle of the atomizer is 35°, the atomization gas pressure is 5-5.5 MPa, the atomization temperature is 1050-1100°C, and the atomization rate is 5-6 kg / min.

[0058] (3) at a temperature of 40 to 45° C., methyl ethyl ketone and hexadecanoic acid are mixed at a mass ratio of 800:1 by volume for 5 minutes to obtain a surface modifier, and then the alloy powder and the surface modifier are mixed in a vacuum mixer at a temperature of 40 to 45° C. for 20 minutes to obtain a modified alloy powder; wherein the mass ratio of the alloy powder to the volume of the organic solvent is 12.5:1.

[0059] (4) In a vacuum mixer at 50-55° C., the modified alloy powder is subjected to removal of organic solvent, the vacuum degree being 70-80 Pa, and the removal time being 8 min, to obtain a copper-based active brazing alloy powder.

[0060] Example 2

[0061] The present embodiment provides a copper-based active brazing alloy powder, whose chemical composition, by mass percentage, includes: 12.0% Sn, 16.0% Ag, 0.8% Al, 4.0% Ti, the total amount of impurity elements is less than 0.3%, and the rest is copper.

[0062] The difference between this embodiment and embodiment 1 is that: at a temperature of 40-45° C., ethanol and hexadecanoic acid are mixed at a mass ratio of 80:1 by volume for 5 minutes to obtain a surface modifier, and the other preparation steps and parameters are the same as those in embodiment 1.

[0063] Example 3

[0064] This embodiment provides a copper-based active brazing alloy powder, the microscopic morphology of which is shown in FIG. Figure 1 As shown, its chemical composition, by mass percentage, includes: 17.0% Sn, 18.0% Ag, 1.0% Al, 4.5% Ti, the total amount of impurity elements is less than 0.3%, and the rest is copper.

[0065] The difference between this embodiment and embodiment 1 is that: at a temperature of 40-45° C., acetone and palmitic acid are mixed at a volume ratio of 100:1 for 3 minutes to obtain a surface modifier, and other preparation steps and parameters are the same as those in embodiment 1.

[0066] Example 4

[0067] The present embodiment provides a copper-based active brazing alloy powder, whose chemical composition, by mass percentage, includes: 10.0% Sn, 19.0% Ag, 0.5% Al, 4.0% Ti, the total amount of impurity elements is less than 0.3%, and the rest is copper.

[0068] The difference between this embodiment and embodiment 1 is that the atomization temperature is 950-1000° C. and the temperature is 40-45° C., and the acetone volume and palmitic acid mass ratio is 160:1 and mixed for 3 minutes to obtain a surface modifier. The other preparation steps and parameters are the same as those in embodiment 1.

[0069] Example 5

[0070] The present embodiment provides a copper-based active brazing alloy powder, whose chemical composition, by mass percentage, includes: 14% Sn, 17% Ag, 1.0% Al, 6.0% Ti, the total amount of impurity elements is less than 0.3%, and the rest is copper.

[0071] The difference between this embodiment and embodiment 1 is that: at a temperature of 40-45° C., acetone and methyl palmitate are mixed at a mass ratio of 120:1 by volume for 3 minutes to obtain a surface modifier, and the other preparation steps and parameters are the same as those in embodiment 1.

[0072] Comparative Example 1

[0073] This comparative example provides a copper-based active brazing alloy powder, whose chemical composition, by mass percentage, includes: 14% Sn, 15% Ag, 1.2% Al, 5.0% Ti, the total amount of impurity elements is less than 0.3%, and the rest is copper.

[0074] The method for preparing the copper-based active brazing alloy powder comprises the following steps:

[0075] (1) Metal copper, metal tin, metal silver, metal aluminum, and metal titanium are placed in a vacuum induction furnace. Under medium frequency induction mode (80-90 kW, 900-1050 Hz) and vacuum degree of 20-30 Pa, the raw materials are completely melted and stirred for 10 minutes to obtain a homogenized alloy melt.

[0076] (2) High-purity argon (purity ≥ 99.999%) is used to vacuum gas atomize the homogenized alloy melt to obtain alloy powder. The microscopic morphology is shown in the figure Figure 2 As shown; the spray angle of the atomizer is 35°, the atomizing gas pressure is 5-5.5MPa, the atomizing temperature is 1050-1100°C, and the atomizing rate is 5-6kg / min.

[0077] Comparative Example 2

[0078] This comparative example uses commercial BCuSnTi active brazing alloy powder, the microscopic morphology of which is shown in the figure below. Figure 3 As shown, its chemical composition, by mass percentage, includes: 19% Sn, 10.0% Ti, the total amount of impurity elements is less than 0.3%, and the rest is copper, referring to the group standard T / CWAN 0085-2022.

[0079] Comparative Example 3

[0080] This comparative example uses commercial BAgCuTi active brazing alloy powder, whose chemical composition, by mass percentage, includes: 28% Cu, 4.0% Ti, the total amount of impurity elements is less than 0.3%, and the rest is silver.

[0081] The copper-based active brazing alloy powder obtained in the above embodiments and comparative examples was tested for melting characteristics, and the results are shown in Table 1. Further, the copper-based active brazing alloy powder obtained in the above embodiments and comparative examples was applied to a silicon nitride ceramic copper-clad substrate (substrate size: 138 mm x 190 mm, copper clad thickness: 0.3 mm, test equipment and conditions: ultrasonic scanning microscope, resolution 50 μm), and brazing void rate and peel strength tests were performed, and the test results are shown in Table 2.

[0082] Table 1 Characteristics and oxidation resistance test of brazing alloy powders with different compositions

[0083]

[0084] Table 2 Test of brazing silicon nitride ceramic copper-clad substrate with different compositions of brazing alloy powder

[0085]

[0086] As shown in Tables 1 and 2, compared with the copper-based active brazing alloy powder in the comparative example, the bulk density of the copper-based active brazing alloy powder prepared in the present invention is lower than 4.6 g / cm 3 , increased to more than 5.3g / cm 3 , an increase of more than 15%; the Hall flow rate has been significantly reduced, and the lower the Hall flow rate value, the better the fluidity of the powder. When the alloy powder is directly exposed to the same environment, the oxygen increment of the powder shows that the oxidation resistance of the surface modified alloy powder has been significantly enhanced; and when applied to silicon nitride ceramic copper-clad substrates, the brazing void rate is significantly reduced and the peel strength is well improved.

[0087] As far as the copper-based active alloy powder preparation process is concerned, powder adhesion and agglomeration are prone to occur during the smelting and atomization process. This is also the direct reason why the commercially available powder in Comparative Example 2 and the unmodified atomized powder in Comparative Example 1 have serious powder agglomeration, small powder bulk ratio, and no fluidity as can be seen from the microscopic morphology diagram. The present invention can significantly improve the above-mentioned powder agglomeration phenomenon, powder bulk ratio, fluidity and other performance indicators through surface modification of the powder. It is crucial to the fineness, dispersibility and uniformity in the subsequent powder preparation process of the paste.

[0088] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A copper-based active brazing alloy powder, characterized in that: The composition includes the following components in terms of mass percentage: 55.0% to 68.0% copper, 6.0% to 17.0% tin, 5.0% to 20.0% silver, 1.0% to 10.0% titanium, 0.1% to 2.0% aluminum, and the total amount of impurity elements is less than 0.3%.

2. The copper-based active brazing alloy powder according to claim 1, characterized in that: The composition includes the following components in terms of mass percentage: 55.0% to 68.0% copper, 6.0% to 17.0% tin, 5.0% to 19.0% silver, 1.0% to 10.0% titanium, 0.1% to 2.0% aluminum, and the total amount of impurity elements is less than 0.3%.

3. The copper-based active brazing alloy powder according to claim 1, characterized in that: The composition includes the following components in terms of mass percentage: 55.0% to 68.0% copper, 6.0% to 17.0% tin, 5.0% to 19.0% silver, 2.0% to 9.0% titanium, 0.1% to 2.0% aluminum, and the total amount of impurity elements is less than 0.3%.

4. A method for preparing a copper-based active brazing alloy powder according to any one of claims 1 to 3, characterized in that: The steps include: S1. Place copper, tin, silver, aluminum and titanium in a vacuum medium frequency induction furnace for smelting, and stir the raw materials after melting to obtain an alloy melt; S2. The alloy melt is vacuum atomized using high-purity argon gas to obtain an alloy powder; S3. The surface modifier obtained by mixing the organic solvent and the modifier is mixed with the alloy powder in a vacuum mixer to obtain a modified alloy powder; S4. Remove the organic solvent from the modified alloy powder to obtain copper-based active brazing alloy powder.

5. The method for preparing a copper-based active brazing alloy powder according to claim 4, characterized in that: In step S1, the melting temperature is 1100-1200°C, the vacuum degree is ≤40Pa, and the stirring time after the raw materials are melted is 5-30min.

6. The method for preparing a copper-based active brazing alloy powder according to claim 4, characterized in that: In step S2, the purity of high-purity argon gas is ≥99.999%; the spray angle of the atomizer is 30° to 50°, the atomization gas pressure is 3 to 7 MPa, the atomization temperature is 900 to 1150°C, and the atomization rate is 4 to 6 kg / min.

7. The method for preparing a copper-based active brazing alloy powder according to claim 4, characterized in that: In step S3, the organic solvent includes one or more of methyl ethyl ketone, ketone, ethanol, acetone, and ether, and the modifier includes one or more of hexadecanoate, methyl palmitate, stearic acid, and palmitic acid; the ratio of the volume of the organic solvent to the mass of the modifier is 50 to 1100:1; and the ratio of the mass of the alloy powder to the volume of the organic solvent is 6 to 20:

1.

8. The method for preparing a copper-based active brazing alloy powder according to claim 4, characterized in that: In step S3, the temperature is 30-45°C; the mixing time of the organic solvent and the modifier is 2-10 minutes; and the mixing time of the surface modifier and the alloy powder is 15-30 minutes.

9. The method for preparing a copper-based active brazing alloy powder according to claim 4, characterized in that: In step S4, the removal temperature is 40-65° C., the vacuum degree is 50-100 Pa, and the removal time is 5-20 min.

10. Use of the copper-based active brazing alloy powder according to any one of claims 1 to 3 or the copper-based active brazing alloy powder obtained by the preparation method according to any one of claims 4 to 9 in the field of brazing, characterized in that: The brazing field includes the fields of ceramic copper-clad substrates, diamond tools, ceramics and Kovar alloys.

Citation Information

Patent Citations

  • Silver-copper-titanium active soldering paste

    CN107322187A

  • Multi-element copper-based alloy brazing filler metal containing rare earth elements, preparation method and brazing method of multi-element copper-based alloy brazing filler metal

    CN114055012A

  • Brazing filler metal paste and welding method using it

    JP1996164494A

Cited By

  • Strip-shaped silver-copper-tin-titanium active brazing filler metal and preparation method thereof

    CN121339760A